2020
DOI: 10.7150/ijms.48046
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model of offspring congenital heart disease based on maternal risk factors during pregnancy: a hospital based case-control study in Nanchong City

Abstract: Objective: Based on epidemiological field data, this study was to develop a prediction model which can be used as a preliminary screening tool to identify pregnant women who were at high risk of offspring congenital heart disease (CHD) in Nanchong City, and be beneficial in guiding prenatal management and prevention. Methods: A total of 367 children with CHD and 367 children without congenital malformations aged 0 to 14 years old were recruited from the Affiliated Hospital of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The association between maternal folic acid as well as multivitamin supplementation and the risk of offspring CHD was controversial (19,22,23). The protective effect of maternal folic acid and multivitamin supplementation against offspring CHD may be because folic acid and multivitamin have antagonistic effects on the process of vascular disruption, and have a rescue effect on apoptotic cells with folic acid deficiency (6). Offspring of our study conceived through assisted reproductive technology was more likely to develop CHD compared with those conceived spontaneously (20).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The association between maternal folic acid as well as multivitamin supplementation and the risk of offspring CHD was controversial (19,22,23). The protective effect of maternal folic acid and multivitamin supplementation against offspring CHD may be because folic acid and multivitamin have antagonistic effects on the process of vascular disruption, and have a rescue effect on apoptotic cells with folic acid deficiency (6). Offspring of our study conceived through assisted reproductive technology was more likely to develop CHD compared with those conceived spontaneously (20).…”
Section: Discussionmentioning
confidence: 64%
“…Congenital heart disease (CHD) is the most common structural birth defect with an incidence rate of 6-12 per 1,000 newborns (1)(2)(3)(4), and its estimated prevalence is about 19-20 per 1,000 newborns when the bicuspid aortic valve is included (5,6). In China, a national study reported an overall CHD prevalence of 9 per 1,000 newborns (7), and it remains the leading noninfectious cause of death in infancy and childhood despite tremendous progress in surgical therapies (8).…”
Section: Introductionmentioning
confidence: 99%
“…Other predictive models have been developed for birth defects. Based on epidemiological field data, using logistic regression, Liang Y et al developed a prediction model that can be used to identify pregnant women who are at high risk of offspring congenital heart defects in Nanchong City, China [ 30 ]. Wang JF et al collected socioeconomic and geographical factors for 7880 live births, and used a support vector machine to develop a prediction model for neural tube defects [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thousands of different birth defects affect the structure or function of fetuses. Most of the clinical studies and predictive models were focused on major birth defects, such as congenital heart defects and neural tube defects [ 30 , 31 , 32 ]. Based on a predictive model for any type of birth defect, we developed a nomogram that can be used as a preliminary screening tool to identify pregnant women at high risk of producing offspring with any birth defects and that can help to guide prenatal management and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge there has been no study assessing the association between DII during pregnancy and CHD risk. Previous studies have evaluated some maternal predictors in pregnancy for CHD [ 14 , 19 , 20 ], giving references for the early prediction of CHD. However, the predictive value of DII for CHD has not been assessed.…”
Section: Introductionmentioning
confidence: 99%